Reintroduction of regulated short selling/securities borrowing and lending (RSS/SBL): Effects on liquidity - Taufil Mohd, Kamarun Nisham; Zaharuddin, Khairul Zharif; Khaw, Lee Hwei (2017)
Purpose - Short selling plays a vital role in price discovery process and increasing market’s liquidity.Malaysia experimented with short selling by permitting it on 3 October 1996 but banning it on 28 August 1997 due to the Asian financial crisis.However, short selling was reintroduced on 26 December 2006.This study is designed to examine the effects of reintroducing short selling on liquidity of the affected stocks.This study also intends to investigate the factors that influence liquidity of the affected stocks.Diamond and Verrecchia (1987) propose that when short-selling is not possible, market would experience an increase in the bid-ask spread and a decline in liquidity.However, the effects of short selling on liquidity are mixed.It is argued that the ban of short selling would adversely affect market liquidity (Beber & Pagano, 2013; Marsh & Payne, 2012).However, there is also evidence where market liquidity declines even when short selling ban is lifted (Baker & Stein, 2004; Chuang & Lee, 2010).Methodology - The stocks allowed for short selling must meet the criteria as outlined by Bursa Malaysia and the list is updated every six month.Additions to and removals from the approved list are common.For the period of this study, from 26 December 2006 to 13 January 2015, 488 additions to and 249 withdrawals from the list were observed.Announcements of inclusions into or withdrawals from the approved list are used as the event dates. Event study methodology and regression analyses are used to achieve the objectives of this study.Liquidity, as measured by using Amihud’s (2002), is used in this study. Findings/Results - The level of abnormal liquidity increases around the announcement day of stock inclusion.The level of abnormal liquidity also increases when stocks are excluded from the short selling list.In addition, liquidity for stock inclusions can be negatively explained by growth opportunity and positively by firm size. Overall the evidence on liquidity suggests that investors welcomed the move to allow short selling.